COUNSELING ON ERGONOMICS CONCEPTS IN THE LEARNING PROCESS IN HIGH SCHOOL AND VOCATIONAL SCHOOL, WASKITO EDUCATION FOUNDATION, SOUTH TANGERANG - Sahat Sinambela; Muhammad Irvan; Argi T; Hermanto R; Dian J P (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2023)
Sitting posture that is not ergonomic can cause various health problems, especially low back pain (LBP), Spinal deformities resulting from incorrect sitting positions, namely scoliosis, kyphosis and lordosis, so there is a need for education to the general public as a whole. especially for Waskito High School and Vocational School children who are still growing. This socialization activity was carried out by explaining the risk of damage to the spine due to sitting incorrectly, causing deviations from the ideal body shape and back pain, by providing direct demonstrations of sitting positions and conditions and then providing discussions and questions and answers with the participants. Based on the results of activities carried out at SMA and SMK, the Waskito Education Foundation was able to understand in detail, good sitting position, the results of discussions and questions and answers with 146 participants consisting of 85 students, and 61 female students participating in Class Science-1. 38, Science-2 . 38, Multi Media-1. 41, and Multimedia-2. 39, it was found that 83% of participants were able to provide responses and understanding regarding the counseling material that had been conveyed from photos before and after the counseling was carried out. Direct counseling with target partners increases knowledge so that it becomes an effective alternative in preventive efforts to prevent spinal disorders (LBP) in participants.